Education in Bhutan : culture, schooling, and Gross National Happiness - Schuelka, Mathew; Maxwell, T.W. (Singapore : Springer, 2016)
This book is a valuable resource not only for those specifically interested in education in Bhutan, but for anyone with an interest in South Asian studies, general Asian studies, educational development, comparative education, Buddhist education, and the Gross National Happiness development philosophy.
Includes bibliographical references and index.
Keywords: Education -- Bhutan; EDUCATION -- Educational Policy & Reform -- General; EDUCATION -- Organizations & Institutions